Ontela PicDeck (A) : customer segementation, targeting, and positioning - Sawhney, Mohanbir S., (SAGE knowledge. Cases., 2016)
Ontela, a technology start-up company, has introduced an innovative service called PicDeck that improves the mobile imaging experience for wireless subscribers. Ontela sells PicDeck to wireless carriers, who in turn private-label the service to their subscribers. Ontela must decide which customer segments it should target for the service and how to create a positioning strategy and a marketing communication plan to promote it. It must also consider the value proposition of the PicDeck service for wireless carriers (its direct customers), who need to be convinced that the service will lead to higher monthly average revenue per user (ARPU) and/or increased subscriber loyalty. Part A of the case provides qualitative information on customer personae that represent different customer segments.